Epistemologi Tafsir Al-Nur Karya M. Hasbi Ash-Shiddieqy Dalam Memahami al-Quran - M. Rifaki Asy'ari (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2021)
This article examines the epistemology of Tafsir Al-Nur by M. Hasbi Ash-Shiddieqy in understanding the Qur'an as well as the contribution of Hasbi's own musician in the interpretation that gave rise to indonesian fiqh. This assessment is descriptive-analytical with a focus on his exegesis, Tafsir Al-Quranul Majid al-Nur which covers several aspects of epistemological studies. From the studies conducted, it can be known that the method of interpretation carried out by Hasbi is classified as analytical-contextual to the texts of the Qur'an, especially related to legal verses then connected with the state of the Indonesian nation today. Even the sources of reference to the interpretation of the tessebut are taken from the books of the muktabarah very closely with the discussion of fiqh universally. Thatsanya as a mufaasir Nusantara, Hasbi berahsil presents interpretation in the context of Indonesianness. This interpretation is certainly not separated from the scientific discipline and culture of Indonesian society. This thought greatly contributed to building the civilization of this nation and adding scientific wisdom in the Islamic world.